The success of glaucoma therapy in diabetes mellitus and non-diabetes mellitus - Nur Shani Meida; Ahmad Ikliluddin; Yunani Setyandriana; Ilma Naafisa Anthrasita (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2022)
ABSTRACT  Glaucoma is a disease marked with damage to the optic nerve, chronic and can cause blindness. Glaucoma needs regular therapy to prevent blindness. This study was an observational study using a case-control approach. Data were analyzed using the Mann-Whitney test to determine the differences in blood sugar levels in the DM and non-DM groups and the Chi-Square test to determine differences in the success of glaucoma therapy in DM and non-DM patients. There were 66 samples of glaucoma patients in this study, consisting of 14 men (21.2%) and 52 women (78.8%). The mean age of the patients was 61.12 ± 9.17 years. The sample was divided into 2 groups, namely 34 DM patients (51.5%) and 32 non DM patients (48.5%). The Mann-Whitney test showed significant differences in blood sugar levels between the DM and non-DM groups (p <0.05). Blood sugar levels in the DM group were 202.59 ± 73.5 mg / dL and in the non-DM group was 106.19 ± 16.3 mg / dL. In conclusion, there is no difference in the success of glaucoma therapy in DM and non-DM patients. Keywords             : glaucoma, glaucoma therapy, diabetes mellitusCorrespondence        :nurshani_meida@yahoo.com